2007
DOI: 10.1007/s12014-007-9000-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Studies of Saliva: A Proposal for a Standardized Handling of Clinical Samples

Abstract: Background In recent years, differential analysis of proteins from human saliva, i.e., proteomic analysis, has received much attention mainly due to its unstressful sampling and its great potential for biomarker research. It is widely considered that saliva is a highly stable medium for proteins thanks to a large amount of antiprotease agents, even at ambient and physiological temperatures. Objective To find the best protocol for the handling of samples, we have investigated the stability of saliva proteins st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Tear, plasma, and saliva samples from both healthy and KC participants were processed for western blot analysis, as previously described (Chertov et al, 2004;Chevalier et al, 2007;Khurshid et al, 2017;Priyadarsini et al, 2014). Briefly, Bradford assay (Thermo scientific, IL, USA) was carried out to determine the protein concentration and purity of saliva and plasma samples, though not to tear samples due to small volume (~5ul).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Tear, plasma, and saliva samples from both healthy and KC participants were processed for western blot analysis, as previously described (Chertov et al, 2004;Chevalier et al, 2007;Khurshid et al, 2017;Priyadarsini et al, 2014). Briefly, Bradford assay (Thermo scientific, IL, USA) was carried out to determine the protein concentration and purity of saliva and plasma samples, though not to tear samples due to small volume (~5ul).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Shorter storage times, lower storage temperatures, with the addition of the enzyme inhibitor, and removal of large material, are all concluded to be beneficial. [122,259] In alignment with the previous mass spectrometry report of Schipper et al, [27,260] the authors conclude, "In case of a clinical comparison with a pathological condition, control saliva samples should be collected from a healthy nonsmoking subject, in the morning, at least 2 h after eating, and the mouth should be rinsed with water. After collection, saliva samples should be stored in a freezer at À20 C, and during sampling, saliva should be kept on ice with a protease inhibitor cocktail and centrifuged to remove insoluble material and then stored at À80 C." Buchan et al [157] have recently reported minimal spectral changes in saliva analysis, with RS, over a seven day period when stored at room temperature.…”
Section: Storagementioning
confidence: 81%
“…[119] In a recent review detailing nanophotonic approaches to pharmaceutical monitoring via Raman, Frosch et al [120] mention saliva as a potential breakthrough diagnostic biofluid. Previously, Butler et al [12] set out a protocol for Raman studies with biological materials, and Henson and Wong [121] outlined the optimal procedures in the collection, storage and the processing of saliva samples in the context of oral biology, while Chevalier et al [122] provided recommendations on storage in a detailed study into proteomic longevity. Despite this literature, there is much room for researchers to take different approaches in setting up their Raman-saliva experiments and the methods they follow, and therefore, a summary of these details would be helpful.…”
Section: Current Analysis Methodsmentioning
confidence: 99%
“…A promising solution to by-pass this issue would rely on the use of aliquots of PreservCyt specimens taken within two days from collection and stored at -80°C [25,27,28]. This approach would be certainly easy to achieve in clinical settings too.…”
Section: Discussionmentioning
confidence: 99%